Cerebral multicystic lesions in a child with neurofibromatosis - İsikay, Sedat (BMJ Publishing Group, 2013)
Neurofibromatosis type 1 (NF-1) is an autosomal dominant neurocutaneous syndrome, with frequent involvement of the central nervous system (CNS). As well as abnormal cellular differentiation, disordered cell migration during development is the most common cause of the various brain lesions. Cystic lesions are rarely observed in neurocutaneous diseases, and the origin of the cysts is not known. This paper presents a rare case, a child at the age of 3, who was diagnosed as NF-1 and was observed to have asymptomatic cystic lesions in right temporal lobe in radiological examination of CNS. This study draws attention to the relationship between these rare cystic lesions of unknown origin and neurocutaneous diseases.